Enhancing the energy absorption capacity of Ti–6Al–4V lattice structure manufactured by additive manufacturing through β-annealing - Yi Ren; Wei Ran; Yongxun Li; Bowen Xue; Wei Chen (Journal of Materials Research and Technology)
The geometric configuration and microstructure are crucial for the mechanical properties of the lattice structure formed by laser powder bed fusion (LPBF). In this study, a type of Ti–6Al–4V lattice structure with hexagonal-body-centered (HBC) structure was fabricated by LPBF and post β-annealing treatment. The microstructure, mechanical properties, energy absorption properties and deformation behavior of the Ti–6Al–4V HBC lattice structure was investigated by electron backscatter diffraction (EBSD), quasi-static compression tests and digital image correlation (DIC) techniques. The results showed that the β-annealing sample completely transformed from the αʹ martensitic microstructure to a completely stable α + β lamellar microstructure, which slightly reduced the ultimate compressive strength of the HBC lattice structure and increased the strain at the end of yielding. The β-annealed sample showed better plasticity and work-hardening rate during the loading process, which increased its absorption capacity by 74.7% compared to the un-annealed sample. Finally, the quantitative analysis of fracture morphology indicated that the HBC lattice structure subjected to β-annealing undergoes ductile-brittle fracture, significantly improving its deformation stability.